2022
DOI: 10.1103/physreva.106.012204
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation and robustness of the quantum mean-force Gibbs state

Abstract: We introduce a numerical method to determine the Hamiltonian of Mean Force (HMF) Gibbs state for a quantum system strongly coupled to a reservoir. The method adapts the Time Evolving Matrix Product Operator (TEMPO) algorithm to imaginary time propagation. By comparing the real-time and imaginary-time propagation for a generalized spin-boson model, we confirm that the HMF Gibbs state correctly predicts the steady state. We show that the numerical dynamics match the polaron master equation at strong coupling. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…MPO算法推广到多个浴的情况 [59] . Ye和Chan [60] 在2021年研究了更复杂浴下的影响泛函的张量网 络构造方法. Chiu等 [61] 在2022年将TEMPO算 法 应 用 到 虚 时 演 化 的 情 况 .…”
Section: 放系统中关联函数的方法 该方法给出的关联函数 是非马尔可夫的 因此超越了通常使用的量子回归unclassified
“…MPO算法推广到多个浴的情况 [59] . Ye和Chan [60] 在2021年研究了更复杂浴下的影响泛函的张量网 络构造方法. Chiu等 [61] 在2022年将TEMPO算 法 应 用 到 虚 时 演 化 的 情 况 .…”
Section: 放系统中关联函数的方法 该方法给出的关联函数 是非马尔可夫的 因此超越了通常使用的量子回归unclassified
“…Specifically, when considering a system strongly coupled to an environment, its thermal state is described by a "Hamiltonian of mean force" that accounts for the environmental interaction. In those cases where this effective Hamiltonian is known [10,[58][59][60][61], the correction to the bare Hamiltonian is also quadratic rather than linear. It is tempting to speculate that these two phenomena may be related to each other.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the thermal equilibrium state is described by the mean force (Gibbs) state, which has been studied comprehensively in the classical and quantum regime for one-dimensional and isotropic three-dimensional interactions with the environment [11][12][13][14][15]. Recently, it has been shown that for the one-dimensional θ -angled spin-boson model, the quantum mean force state becomes precisely the classical mean force state in the large-spin limit [16].…”
Section: Introductionmentioning
confidence: 99%